HUBUNGAN PERSONAL HYGIENE DAN SANITASI LINGKUNGAN TERHADAP INFEKSI CACING PADA ANAK USIA 6 – 12 TAHUN YANG TINGGAL DIPINGGIRAN ALIRAN SUNGAI SIAK - Yoza Dwi Saputra; Riri " Novayelinda; Bayhakki " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Personal hygiene and environmental sanitation are important factors in health care efforts to avoid worm infections. Intestinal helminth infection is the most common chronic infection of school-aged children. High and low frequency of worms associated with personal hygiene and environmental sanitation. This study aims to determine the relationship between personal hygiene and environmental sanitation to worm infections in children aged 6-12 years who live in the flow of Siak river. This research used descriptive correlation design with cross sectional approach. This study was conducted with the number of samples of 47 respondents of children aged 6-12 years who were taken according to inclusion criteria by using cluster sampling technique. To assess personal hygiene using questionnaires and observation sheets to assess environmental sanitation. The analysis used is Chi-Square. The results found there was a relationship between personal hygiene with worm infection (p value 0,000) and no relationship between environmental sanitation with worm infection (p value 0,084). Based on the results of this study recommended children to maintain personal hygiene and good environmental sanitation avoid the worm infection. Keyword: Worms infection, personal hygiene, environmental sanitation,